The ANZAC Tribulations at Gallipoli in Recent Australian Children’s Literature - Hervé Cantero (Anglica. An International Journal of English Studies)
Generations of Australian children have been presented with iconic figures and values associated with the events of 1915 at Gallipoli and involved in the ritual practices of remembrance exemplified by Anzac Day ceremonies throughout a corpus of children’s literature which ranges from picture books for pre-schoolers to young adult fiction. This paper aims to broadly identify the narrative strategies at work in a selection of recent stories of brave animals helping the Aussie boys under fire or paeans to the duty of personal and communal remembrance and to examine them in a larger context of national self-representation.